Scientific Competition - Albert, Max; Voigt, Stefan; Schmidtchen, Dieter (Mohr Siebeck, 2008)
Is science a 'market of ideas'? Not according to the economics of science. Science is competitive, but scientific competition is not market competition. Nor is scientific competition the same as competition between universities. Scientific competition is, first of all, competition between individual scientists. Current science policies shift the boundary between scientific competition, where scientists provide public goods in the hope to acquire status among their peers, and market competition in science, where the results of research are private property protected by patents or other means, in favor of the market. However, the economic ring of the political slogans cannot conceal a serious lack of understanding of scientific competition behind the reform proposals.